2013
DOI: 10.1016/j.rmed.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic paralysis in Veterans with COPD

Abstract: Summary Background Chronic Obstructive Pulmonary Disease (COPD) is a common disorder of Veterans that causes significant morbidity and mortality. To measure Veterans’ perceptions about COPD, the effect of COPD on their lives and health, and their needs for improved health, we performed a postal survey. Methods 3263 Veterans with a diagnosis of COPD who received care at the Cincinnati Veterans Affairs Medical Center in 2008 were stratified into quintiles by Veterans Health Administration - associated COPD he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…All 50 subjects completed a questionnaire based upon the COPD Health Determinants survey. 13 Ninety-two percent of subjects received all of their care at the Cincinnati VAMC. Thirty-seven (74%) reported that they took their inhalers as prescribed, and 34 (68%) previously received inhaler use instruction.…”
Section: Subjects' Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 50 subjects completed a questionnaire based upon the COPD Health Determinants survey. 13 Ninety-two percent of subjects received all of their care at the Cincinnati VAMC. Thirty-seven (74%) reported that they took their inhalers as prescribed, and 34 (68%) previously received inhaler use instruction.…”
Section: Subjects' Survey Resultsmentioning
confidence: 99%
“…Then they viewed the videos for those inhalers and were retested in a similar fashion as the providers. At the initial encounter, subjects completed a demographics questionnaire, COPD Health Determinants survey, 13 and the COPD Assessment Test. 14 After 3-6 months,…”
Section: Provider and Subject Data Collectionmentioning
confidence: 99%